Income taxation and labour response: Empirical evidence from a DID analysis of an income tax treatment in Italy - Bruno Bosco; Carlo Federico Bosco; Paolo Maranzano (Fondazione Eni Enrico Mattei (FEEM), 2024)
This paper uses the Italian income tax treatment of 2006/7 as a quasi-natural tax experiment to offer some fresh empirical evidence on how labour supply responds to exogenous income tax hikes. We adopt the identification strategy based on TWFE panel data Difference-in-Differences (DID) model to define the correct statistical framework of the study, and to benefit from the specific features of the above tax experiment, namely homogeneity and contemporaneity of the treatment. Results show that the extensive negative adjustments of various response variables measuring the supply of labour services offered by treated taxpayers are statistically significant, rapid, and strong but not long-time lasting. Not surprisingly, we also find that that treated families reduce in a similar manner their consumption with respect to families in the control groups. Analogous adjustment responses to tax hikes characterise the growth of per-capita regional GDP. The estimated aggregate effects of tax hikes are further compared with the spatial-temporal patterns observed for every response variable in treated and untreated regions.
Keywords: C10; C18; C21; H2; E2; E32; E62; C23; C26; 330; Income Taxation; Extensive labour supply change; TWFE Panel Data DID; Convergence tests; Taxation and regional growth